Factors leading to effective social participation promotion interventions for people with intellectual disability: a protocol for a systematic review - Andrés Aparicio (Systematic Reviews, 2021)
Abstract Background People with intellectual disabilities have been historically excluded from decision-making processes. Previous literature indicates that increasing social participation may be an effective way to address this exclusion, but no systematic review of interventions designed to increase social participation of people with intellectual disabilities have been conducted. This study aims to identify and organize the factors associated with interventions that increase the social participation of people with intellectual disabilities and to provide a set of best of practices for future interventions. Methods/design The databases Web of Science, Scopus, LILACS, and PubMed will be searched for articles from January 2004 onwards; grey literature search will be identified through searching additional databases (such as Google Scholar and EBSCO databases). Randomized controlled trials, nonrandomized controlled trials, and controlled pre–post studies will be included. Noncontrolled pre–post studies will also be included. Observational or qualitative studies will be excluded. The primary outcomes are measures of social participation. Secondary outcomes include measures of well-being, stigma, knowledge about rights, and advocacy processes. Two reviewers will independently screen articles, extract relevant data, and assess the quality of the studies. We will provide a meta-analysis of included studies if possible, or a quantitative narrative synthesis otherwise. Discussion This systematic review will add to our understanding of effective social participation interventions for people with intellectual disability. It will allow us to identify and organize which factors lead to an increase in social participation and help us define a set of best practices to be followed by future interventions. Systematic review registration PROSPERO CRD42020189093